2021
DOI: 10.1155/2021/9409785
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Quad-Port UWB MIMO Antenna for Body-Worn Applications

Abstract: A conformal four-port multiple-input-multiple-output (MIMO) antenna operating at 2.4 GHz and ultrawideband (UWB) is presented for wearable applications. The unit element of the MIMO antenna is a simple rectangular monopole with an impedance bandwidth of 8.9 GHz (3.1–12 GHz). In the monopole radiator, stubs are introduced to achieve 2.4 GHz resonance. Also, a defect is introduced in the ground plane to reduce backside radiation. The efficiency of the proposed antenna is greater than 95%, and its peak gain is 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The proposed integrated antenna in the BLE sensor is fabricated and tested with an outstanding performance in terms of bandwidth, gain, efficiency, and SAR. As we can see from the table, [9,24] and this work have the highest efficiency and smallest SAR compared to the related works. However, our antenna gain is higher than the wearable antenna in [9,24] while antenna efficiency in [24] is higher but its bandwidth is narrower than this work.…”
Section: Integrated Antenna Inmentioning
confidence: 70%
See 1 more Smart Citation
“…The proposed integrated antenna in the BLE sensor is fabricated and tested with an outstanding performance in terms of bandwidth, gain, efficiency, and SAR. As we can see from the table, [9,24] and this work have the highest efficiency and smallest SAR compared to the related works. However, our antenna gain is higher than the wearable antenna in [9,24] while antenna efficiency in [24] is higher but its bandwidth is narrower than this work.…”
Section: Integrated Antenna Inmentioning
confidence: 70%
“…As we can see from the table, [9,24] and this work have the highest efficiency and smallest SAR compared to the related works. However, our antenna gain is higher than the wearable antenna in [9,24] while antenna efficiency in [24] is higher but its bandwidth is narrower than this work. Although antenna [9] efficiency is higher than this integrated antenna, efficiency of [9] will be reduced when it is integrated and tested into circuit.…”
Section: Integrated Antenna Inmentioning
confidence: 70%
“…The power handling capacity and ultra-wideband characteristics of MIMO antennas are further improved by adding DGS [21][22][23]. The two-radiating MIMO structure is stretched to an imposing four-element MIMO radiating structure by folding the arrays towards the antenna front side [24][25].…”
Section: Literature Surveymentioning
confidence: 99%
“…The antenna exhibited stable radiation characteristics and isolation when put on a human body. Govindan T. et al [ 74 ] proposed a rectangular monopole antenna with a DGS, as shown in Figure 14 a. To enhance impedance matching, rectangular slots are cut on either side of the radiator, and U-shaped slots are added to the ground layer.…”
Section: Flexible Uwb Mimo Antennamentioning
confidence: 99%